Tropical forests as a target of global scientific production and the comparative position of Brazil. - Edler de Almeida, Elenara Chaves; Almeida Guimarães, Jorge (Revista Pensamiento Americano)
This research article was focused on the scientific production of the world on the topic Tropical Forests, based on the articles published by the 20 main countries that compose the Web of Science Data Base, published by Institute for Scientific Information (ISI), which published 90% of the world's total production covering the period 1901 and 2012. The evolution of this production goes from 2 articles in 1901 to 3.554 in the year 2012. The publications in the period are mainly from the USA (14,145 articles) and Brazil (8,324 articles), corresponding the sum of the two countries to 60% of the total publications. The expansion is credited to a set of factors, highlighting the growing importance of tropical forests as an area of geopolitical interest; ecological and conservationists movements; the availability of new imaging technologies and the very gradual growth of world scientific production in recent years. Environmental sciences / ecology is the area of knowledge that registers the largest number of publications (36.8%), but nine other areas, among them, plant sciences (9.8%), agriculture (7.1%), biodiversity conservation 6.6%) and remote sensing (3.4%) also attracted interest for publications about the subject.